PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY (ROE) PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Herlina Herlina; Wiwin Winingsih (Universitas La Tansa Mashiro, 2016)
Return On Equity ratio state is not good then it would indicate that the company is less efficient in the use of their own capital so that the rate of return to shareholders will be smaller. Current Ratio level that is too high is not good, because it reflects the current assets that are not being used effectively and is unable to obtain the maximum profit. The method used is associative method with quantitative descriptive approach. The population is the entire Food and Beverage companies listed in Indonesia Stock Exchange (IDX), which amounted to as many as 13 companies. Samples used as many as 10 companies, in which the sample was drawn using purposive sampling technique. This study using multiple linear regression techniques. The results of this analysis, the Current Ratio significant effect on Return On Equity (ROE), Debt To Equity Ratio no significant effect on Return On Equity (ROE), then the Current Ratio and Debt To Equity Ratio significant effect on Return On Equity (ROE).The conclusion of this study are: 1. Conditions Current Ratio highest value obtained by PT Delta Djakarta (DLTA), the lowest value obtained PT Siantar Top (STTP). Conditions Debt To Equity Ratio highest value obtained PT Mayora Indah (MYOR). The lowest scores were obtained by PT Delta Djakarta (DLTA) is 0.22. Conditions Return On Equity highest value obtained by PT Delta Djakarta (DLTA). The lowest value was obtained PT Sekar Laut (SKLT). 2. Current Ratio significant effect on Return On Equity (ROE) on Food And Beverage companies listed in Indonesia Stock Exchange (BEI) in the period 2011-2015. 3. Debt To Equity Ratio no significant effect on Return On Equity (ROE) on Food And Beverage companies listed in Indonesia Stock Exchange (BEI) in the period 2011-2015. 4. Current Ratio and Debt To Equity Ratio significant effect on Return On Equity (ROE) on Food And Beverage companies listed in Indonesia Stock Exchange (BEI).